Puzzled indemnity [large type] : a Puzzle Lady mystery - Hall, Parnell (Hall, Parnell. Puzzle Lady mystery., 2015)
"It's been a cold, lonely winter for Cora Felton. Long distance has cooled the Puzzle Lady's on-again-off-again affair with Sergeant Crowley, and the only case Chief Harper has for her to investigate is a routine liquor store robbery. So when her attorney friend Becky asks her to explore the possibility that her client Brittney's philandering husband is planning to murder her for the insurance money, Cora jumps at the chance. She brings in her loathsome ex-husband Marvin to play blackmailer and prove the affair. But when Brittany's husband is killed by a car bomb right outside the Bakerhaven police station, and it turns out she had insurance on him, the police arrest her for murder. To save Becky's clueless client from the clutches of the law, Cora will manipulate a TV reporter, cast suspicion on an innocent man, crack crossword and Sudoku clues, solve the liquor store robbery, and enlist the aid of both Sergeant Crowley and his girlfriend in this outragous new entry in the Puzzle Lady Mystery series featuring Sudoku by Will Shortz"--Provided by publisher.